2018
DOI: 10.14419/ijet.v7i4.34.27387
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Tourist Destinations Through Language and Visual Elements on Tourism Websites: A Tourism Discourse Perspective

Abstract: Official tourism website has become an essential aspect in shaping tourist destinations. Tourism websites are an essential tool in shaping the norms and values of the destinations which travelers have to visit — however, only very few research which focused on the integration of the language element and visual element in shaping tourist destination images. Thus, this study aims to investigate how effective is the use of language and visual elements in shaping the tourist destination on the tourism websites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, visual elements such as modality and salience can enhance the destination's image. For example, Salim & Som (2018); Jaworski & Thurlow (2010); investigate the tourism promotional media. They have shown that language plays a vital role in portraying the destination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, visual elements such as modality and salience can enhance the destination's image. For example, Salim & Som (2018); Jaworski & Thurlow (2010); investigate the tourism promotional media. They have shown that language plays a vital role in portraying the destination.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that language plays a vital role in portraying the destination. The studies, however, uncover all critical aspects that construct the tourism discourses, for example, visual elements (Salim & Som, 2018;Liasidou, 2018;Choi et al, 2007;Kress & van Leeuwen, 2006). Language and visual elements enhance the destination image (Samad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%